In Vitro Study: Effect of Cobalt(II) Chloride Against Dengue Virus Type 1 in Vero Cells - Teguh Hari Sucipto; Yovilianda Maulitiva Untoro; Harsasi Setyawati; Anisa Maharani; Novia Faridatus Sholihah; Siti Churrotin; Ilham Harlan Amarullah; Soegeng Soegijanto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Dengue virus (DENV) serotypes DENV-1 to DENV-4 are enveloped viruses that belong to the genus Flavivirus of the Flaviviridae. Dengue vaccine or antiviral has not yet been clinically approved for humans, even though there have been great efforts toward this end. Antiviral activity against DENV is needed to develop to be an alternative drug for DENV virus. Cobalt(II) chloride have been used in the treatment and prevention of diseases of humans since ancient times. The aim of this study is to investigate the antiviral effects and Cytotoxicity of Cobalt(II) chloride. This compound was further investigated for its inhibitory effect on the replication of DENV-1 in Vero cells. Antiviral activity and Cytotoxicity measured by WST-1 assay. The IC50 value of the Cobalt(II) chloride for DENV-1 was 0.38 μg/ml. The cytotoxicity of Cobalt(II) chloride to Vero cell suggest that the CC50 value was 2.91 µg/ml The results of this study demonstrate the anti-dengue serotype 1 inhibitory activity of Cobalt(II) chloride was a high toxic compound.